Academic Journal Publishing and Open Access - Hurme, Pertti (Human Technology, 2015)
Human Technology: An Interdisciplinary Journal on Humans in ICT Environments started in 2005 as an open-access, peer-reviewed academic journal, published only online. At that time, the traditional printed journal model of publishing houses was quite dominant and largely uncontested. Now open-access journal publishing is growing rapidly (Björk & Solomon, 2014) and providing important alternative routes to researchers’ access to the literature in many disciplines. This editorial only discusses the gold model of open-access publishing, not the green model (traditional journal publishing and a parallel repository).